Perbedaan Pandangan Terhadap Pembatasan Hak Dipilih Antara Putusan Mahkamah Konstitusi Dengan Putusan Mahkamah Agung - Qaidah Bazilah Bazlaa; Dian Bakti Setiawan; Feri Amsari (Lareh Law Review, 2023)
In general elections, the public has the right, namely, not to vote, and the right to be elected. The right to be elected is the right of citizens to be elected as members of deliberative bodies or representatives of the people in a general election. Article 240 paragraph (1) letter g of the General Election Law regulates restrictions on the right to vote for former corruption convicts. Regarding the norms in this article, the Constitutional Court and the Supreme Court have different views. This is formulated in the Constitutional Court Decision Number 87/PUU-XX/2022 and the Supreme Court Decision Number 46P/HUM/2018. This article analyzes the views of Constitutional Justices and Supreme Court Justices regarding the norms in article 240, paragraph (1) letter g. The purpose of this article is to find out how voting rights are limited for former corruption convicts. This article uses a normative juridical research method. The research results found that first, restrictions on the right to vote for former convicts may be carried out in the interests of ensuring the freedom of disadvantaged groups. Second, in deciding a decision, the judge is obliged to explore, follow and understand the legal values ​​and sense of justice that exist in society as well as pay attention to the juridical aspect.